First record of Euchromius Ocelleus (Haworth, 1811) (Lepidoptera: Crambidae) in Slovenia - Gomboc, Stanislav (Acta entomologica slovenica (Ljubljana), 2013)
One specimen of Euchromius ocelleus (Haworth, 1811) was found in Kozjanski Park, Slovenia, on September 11th, 2012, at the end of a hot summer period. The specimen was caught on an UV light tent trap during inventory of moths in a sand pit at Gradišče near Župjek, not far from the Croatian border. Since only one specimen was registered so far in Slovenia, it is assumed that this was a migrant which did not reproduce here.
Keywords: Crambidae; fauna; favna; Kozjanski Park; Lepidoptera; metulji; moths; Slovenia; Slovenija